Technologies on display. The Storhaug ship burial (AmS-Skrifter, 2026)
Ship burials were grand events in late Iron Age society. Great efforts were invested to make a spectacle in memory of the deceased ruler and to promote the new rulers. No other single context has provided us with such a wealth of material culture from the period as the Oseberg ship burial. The Storhaug ship burial in southwestern Norway (CE 779) is an early example of the same phenomenon. The article examines the various components in the Storhaug burial to highlight the technologies on display here. In the burial event, imports and exports, weapon technology, metallurgy, food production technology, transportation technology, woodcraft, and construction technology were activated and displayed within the frame of a ritual technology. While most types of technologies in society were represented, it was a conscious selection. In the paper, food production technology and construction technology are explored as examples. The Storhaug burial complex is compared especially with the better-preserved Oseberg and Gokstad burials. Although significant similarities are identified with Oseberg, important differences also show that ship burials were not one set material complex. The focus on various technologies reflected renegotiations of the roles of the king and society, guided by the regional context and traditions.